Growth and reproductive performance of African giant catfish, Heterobranchus longifilis Valenciennes 1840 broodstock on ascorbic acid supplementation - adebayo, olabode thomas; Fawole, Femi John (Indian Journal of Fisheries, 2012)
This study was conducted to determine the effects of different levels of ascorbic acid supplementation on growth, reproductive performance and larval quality of Heterobranchus longifilis female broodstock fishes. Five diets were formulated incorporating ascorbic acid at levels of 0 (control), 50, 100, 150 and 200 mg kg-1. Fish averaging 700 + 2.84 g were randomly fed with the experimental diets for 8 weeks. Fish fed with control diet had lower weight gain than fish fed with ascorbic acid supplemented diets (p>0.05). The total percentage weight gain and specific growth rate in all treatments were significantly different (p